Thai Silk Career Group Promotion - Hoonwongsa, Ariya (Journal for Developing the Social and Community, 2017)
Silk and Thai silk products have long been mentioned in the matter of beauty colors, patterns and weaving. Thai silk products are popular both by Thai and foreigners, so, Thai silk industry can create jobs for villagers and increase income for rural workers which over past several years, silk products have generated revenue of less than five billion baht a year. Therefore, the promotion of Thai Silk Group should be as follows; to support the use of silk from Thailand government, campaign for Thai cloth, promoting and developing contemporary Modern Thai silk products, promotion of marketing channels, improving the quality of the fabric in making the product,